Theoretical Study of 1, 3-Dipolar Cycloadditions Regioselectivity of Benzyl Azide with Glycosyl-O-Acetylene Using Density Functional Theory (DFT) (Communications in Computational Chemistry, 2025)
A theoretical study of 1, 3 cycloaddition has been carried out using densityfunctional theory (DFT) methods at the B3LYP/6-31G* level. The regioselectivity of thereaction have been clarified through different theoretical approaches: Case of aTwo-Center Process (domingo approach), HSAB principle (Gazquez and Mendezapproach), and the activation energy calculations. The analysis of results shows that thereaction takes place along concerted asynchronous mechanism and the isomer meta isfavored, in agreement with the experiment results.
Keywords: 1; 3-dipolar cycloadditions; 1; 2; 3-Triazole; regioselectivity; DFT calculations; Parr Functions.